SOSIALISASI PEMBUATAN MEDIA POP UP PADA GURU-GURU SEKOLAH DASAR NEGERI JOHO 2 SUKOHARJO - Diana Dewi Wahyuningsih; Imam Setya Nugroho (LPPM ITB AAS Indonesia Surakarta, 2021)
There are still many teachers of public elementary school 2, joho sukoharjo, who do conventional learning, so that children quickly feel bored and less interested in learning. This service focuses on developing learning media for public elementary school 2 teachers, joho sukoharjo, in the form of creative and innovative Pop Up Books. The objectives of this activity are: (1) increasing knowledge for public elementary school teachers in Joho 2 Sukoharjo about the learning model and (2) training teachers at state elementary schools in Sukoharjo 2 to make Pop Up Books as an alternative media for learning in schools. Pop Up Book is an interesting and easy to learn learning media because it is designed as a three-dimensional book. The methods used in this activity are lectures, questions and answers, demonstration discussions and assignments. The result of this activity is Pop Up Media created by public elementary school teachers in Joho 2 Sukoharjo, which is indicated by an increase in post-test scores compared to pre-test scores. In addition, teachers are able to develop learning media in the form of Pop Up Books. Keywords: Learning Media, Pop Up Book, SDN 2 Joho Abstrak : Guru-guru sekolah dasar negeri 2 joho sukoharjo, masih banyak yang melakukan pembelajaran dengan konvensional, sehingga anak-anak cepat merasa bosan dan kurang tertarik dalam pembelajaran. Pengabdian ini berfokus pada mengembangkan media pembelajaran pada guru-guru sekolah dasar negeri 2 joho sukoharjo, dalam bentuk Pop Up Book yang kreatif dan inovatif. Tujuan dari kegiatan ini adalah: (1) menambah pengetahuan kepada guru-guru sekolah dasar negeri joho 2 sukoharjo tentang model pembelajaran dan (2) melatih guru-guru sekolah dasar negeri joho 2 sukoharjo untuk membuat Pop Up Book sebagai alternative media pembelajaran di sekolah. Pop Up Book menjadi media pembelajaran yang menarik dan mudah dipelajari karna didesain sebagai buku tiga dimensi. Metode yang digunakan dalam kegiatan ini adalah ceramah, Tanya jawab, diskusi demostrasi dan pemberian tugas. Hasil dari kegiatan ini adalah Media Pop Up hasil karya guru-guru sekolah dasar negeri joho 2 sukoharjo, yang ditunjukkan dengan peningkatan nilai post-test dibandingkan dengan nilai pre-test. Selain itu, guru-guru mampu mengembangkan amedia pembelajaran yang berupa Pop Up Book. Kata kunci: Media Pembelajaran, Pop Up Book, SDN 2 Joho